Cognitive effects of estradiol after menopause: A randomized trial of the timing hypothesis. (16th August 2016) - Henderson, Victor W.; St. John, Jan A.; Hodis, Howard N.; McCleary, Carol A.; Stanczyk, Frank Z.; Shoupe, Donna; Kono, Naoko; Dustin, Laurie; Allayee, Hooman; Mack, Wendy J.
Abstract : Objective: To test the hypothesis that effects of estrogen-containing hormone therapy on cognitive abilities differ between postmenopausal women near to, and further from, menopause. Methods: In this randomized, double-blind, placebo-controlled trial, healthy women within 6 years of menopause or 10+ years after menopause were randomly assigned to oral 17β-estradiol 1 mg/d or placebo. Women with a uterus received cyclic micronized progesterone vaginal gel or placebo. The primary outcome assessed at 2.5 and 5 years, compared between treatment groups, was change in a standardized composite of neuropsychological test scores assessing verbal episodic memory. Secondary outcomes assessed executive functions and global cognition. Results: A total of 567 women were included in modified intention-to-treat analyses after a mean treatment duration of 57 months. For verbal memory, the mean estradiol minus placebo standardized difference in composite scores (−0.06, 95% confidence interval −0.22 to 0.09) was not significant (2-tailed p = 0.33). Differences were similar in early and late postmenopause groups (2-tailed interaction p = 0.88). Interactions between postmenopause groups and differences between treatment groups were not significant for executive functions or global cognition. Conclusions: Estradiol initiated within 6 years of menopause does not affect verbal memory, executive functions, or global cognition differently than therapy begun 10+ years after menopause. Estradiol neither benefits nor harms these cognitive abilities regardless of time since menopause. Classification of evidence: This study provides Class I evidence that estradiol initiated within 6 years of menopause does not affect cognition at 2.5 years differently than estradiol initiated 10+ years after menopause.